Critique of the 2017 epileptic seizure and epilepsy classifications. (28th March 2019) - Lüders, Hans; Akamatsu, Naoki; Amina, Shahram; Baumgartner, Christoph; Benbadis, Selim; Bermeo‐Ovalle, Adriana; Bleasel, Andrew; Bozorgi, Alireza; Carreño, Mar; Devereaux, Michael; Fernandez‐Baca Vaca, Guadalupe; Francione, Stefano; et al.
Summary: This article critiques the International League Against Epilepsy (ILAE) 2015‐2017 classifications of epilepsy, epileptic seizures, and status epilepticus. It points out the following shortcomings of the ILAE classifications: (1) they mix semiological terms with epileptogenic zone terminology; (2) simple and widely accepted terminology has been replaced by complex terminology containing less information; (3) seizure evolution cannot be described in any detail; (4) in the four‐level epilepsy classification, level two (epilepsy category) overlaps almost 100% with diagnostic level one (seizure type); and (5) the design of different classifications with distinct frameworks for newborns, adults, and patients in status epilepticus is confusing. The authors stress the importance of validating the new ILAE classifications and feel that the decision of Epilepsia to accept only manuscripts that use the ILAE classifications is premature and regrettable.